Analisis Hukum Jual Beli Salam dalam Perspektif Imam Syafii - Zakir, Muhammad; Winario, Mohd; Paisal, Paisal (EL-EMIR Institute, 2025)
This study aims to analyze the law of salam sale contracts from the perspective of Imam al-Shafi‘i and to evaluate their relevance to contemporary muamalah (Islamic commercial practices). Salam sale is a form of contract in which payment is made in advance, while the goods are delivered later according to agreed specifications. In the Shafi‘i school of thought, this contract is permitted even though the goods do not yet exist at the time of the agreement, as it is supported by shar‘i evidence and fulfills the practical needs of society in economic activities. The method used in this study is library research with a qualitative approach, analyzing primary sources such as al-Umm by Imam al-Shafi‘i and other fiqh books from the Shafi‘i school, as well as secondary literature from contemporary scholars and academics. The results show that salam sale is permissible according to Imam al-Shafi‘i under specific conditions: full payment must be made at the time of the contract, the goods must have clear, measurable, and mutually known specifications, and the time and place of delivery must be precisely determined. These provisions are intended to avoid elements of gharar (uncertainty) and potential disputes. The study concludes that salam sale remains highly relevant in the modern Islamic economic system, particularly in pre-order schemes, agricultural contracts, and financing in the production sector based on sharia principles.